2009
DOI: 10.1177/0261927x09351679
|View full text |Cite
|
Sign up to set email alerts
|

I Am “Fatter” Than She Is: Language-Expressible Body-Size Comparisons Bias Judgments of Body Size

Abstract: This article proposes and tests a comparison-induced distortion theory account of body-size judgments wherein language-expressible body-size comparisons (e.g., “Jane is fatter than Kimberly” or “Kimberly is thinner than Jane”) bias judgments of body sizes. Study 1 found that when actual differences were small, language-expressible comparisons biased body-size judgments away from the sizes with which they were compared even though the distribution of contextual body sizes was held constant. Study 2 found that w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…These results are consistent with a general framework in which the spatiotemporal structure of language can be tuned to match the structure of the physical world. The result is a communication system which exploits redundancy, allowing a single message to convey multiple types of information: A simple statement of ordinal magnitude carries implications about absolute size (e.g., Choplin, 2010) and, as found in the current studies, about the spatial arrangement of the compared items-and possibly about other things, too.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…These results are consistent with a general framework in which the spatiotemporal structure of language can be tuned to match the structure of the physical world. The result is a communication system which exploits redundancy, allowing a single message to convey multiple types of information: A simple statement of ordinal magnitude carries implications about absolute size (e.g., Choplin, 2010) and, as found in the current studies, about the spatial arrangement of the compared items-and possibly about other things, too.…”
Section: Discussionmentioning
confidence: 77%
“…Clark, 2006;Goodhew, McGaw, & Kidd, 2014;Louwerse, 2011). Previous work has shown that the message-sender's choice of magnitude comparative is influenced by the absolute size of the items (Matthews & Dylman, 2014) and that this choice in turn affects inferences about the sizes of unseen objects (Choplin, 2010;Rusiecki, 1985). However, the information-transmission is imperfect.…”
Section: Magnitude Comparisons Convey Spatial Informationmentioning
confidence: 99%
“…From this perspective, the choice of adjective shapes the semantic information that is activated when forming a comparative judgment, with subsequent effects on people's best estimates of the target quantity. Similarly, Choplin (2010) has found that the choice of comparative adjective {fatter vs. thinner) can affect people's memory for women's body size.…”
Section: The Importance Of Comparative Languagementioning
confidence: 99%
“…Body image refers to “a person’s perceptions, thoughts, and feelings about his or her body” (Grogan, 2008, p. 3). Body image deals with self-perceptions that develop, in part, as a result of comparing one’s body to others’ (Choplin, 2010). Body satisfaction is the degree to which one is content with one’s physical body (Ogden & Clementi, 2010).…”
Section: Body Satisfaction and Communicationmentioning
confidence: 99%